Pengaruh Pembelajaran Proyek Penguatan Profil Pelajar Pancasila (P5) terhadap Pembentukan Karakter Siswa Kelas X pada Pembelajaran Pendidikan Agama Islam - Iriyansyah Iriyansyah; Marsella Marsella; Heri Sepriyadi (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aimed to analyze the implementation of the Strengthening Pancasila Student Profile Project (P5), describe the character development of tenth-grade students in Islamic Religious Education (IRE), and examine the effect of P5 learning on students' character development at SMA Sentosa Bhakti Baturaja. A quantitative approach was employed, with data collected through observation, interviews, questionnaires, and documentation. The study population consisted of 129 tenth-grade students, while a sample of 97 students was selected using the Slovin formula. Research instruments were questionnaires measuring the P5 learning and student character development variables. Data were analyzed through editing, data classification, range and interval determination, frequency distribution, mean, standard deviation, percentage, High-Medium-Low (TSR) categorization, and Chi-Square hypothesis testing. The findings revealed that both the implementation of P5 learning and students' character development were categorized as moderate. The Chi-Square test yielded a value of χ² = 14.743, exceeding the critical values at both the 5% significance level (9.488) and the 1% significance level (13.277). Therefore, the alternative hypothesis was accepted, indicating that P5 learning has a statistically significant effect on the character development of tenth-grade students in Islamic Religious Education at SMA Sentosa Bhakti Baturaja.